Traumatic Events, Personality and Psychopathology in Takotsubo Syndrome: A Systematic Review - Galli, Federica; Bursi, Francesca; Carugo, Stefano (Frontiers in Psychology, 2019)
Objective Takotsubo syndrome (TTS) is a transient heart disease that has been historically related to the occurrence of psychological (emotional) factors (“broken heart” syndrome). We aimed to conduct a systematic review analyzing the role of psychological factors in TTS. Methods All studies on TTS and psychological factors from January 1991 through April 2019 were scrutinized according to the Cochrane Collaboration and the PRISMA statements. Selected studies were additionally evaluated for the Risk of Bias according to the Newcastle-Ottawa Scale (NOS). Results Fifteen case-control studies (by Mayo Clinic criteria) were finally selected. Most studies analyzed stressful life-events or trauma, although with conflicting findings, while a likely role of long-lasting psychological distress seemed to be a homogenous result. Among life-time psychopathology, only anxiety appeared to have a significant role. Some studies outlined a likely role of personality, but findings are conflicting. Conclusion Our findings do not lead to any definitive assumption on the specific role of psychological factors in TTS, also for scant strong methodology of the most part of the studies. More studies with stronger research methodology are needed to better characterize psychological elements in TTS.